People with intellectual disabilities and borderline intellectual functioning in the Spanish criminal justice system - L Gómez-Durán, Esperanza (Criminology & criminal justice, 2025)
The way criminal responsibility modifications are applied in intellectual disability and borderline intellectual functioning cases remains empirically unexplored in Spain. We retrieved 100 IQ assessments that involved criminal proceedings, Spanish adult defendants, intelligence quotient testing and intellectual disability/borderline intellectual functioning diagnoses. Intellectual disability and borderline intellectual functioning were diagnosed in 26% and 74% of cases. Intellectual disability diagnoses were significantly associated with forensic doctor support for lack of capacity to be found guilty because of intellectual impairment. Criminal responsibility was modified in 65.8% of convictions and a safety measure was dictated in 10.1%. Courts’ decision of modified responsibility because of intellectual impairment was positively associated with the defendant’s IQ, the forensic diagnosis, the forensic opinion about impaired capacity to be found guilty and the Prosecutor’s position. Any level of intellectual impairment deserves a forensic assessment because of its potential impact on criminal responsibility. Yet, safety measures are underused, so a unique opportunity to help is being missed.